Differences in rehabilitation for high-risk newborns: The impact of neonatal intensive care unit hospitalization - Kyoung Yee Kang; Eun Sil Kang; Hye-Kang Park; Seung Been Hong; Ha Lim Lee (PLoS ONE, 2025)
There is growing recognition of the importance of rehabilitation through immediate and long-term follow-up, and neonatal intensive care unit (NICU) aftercare is emerging as an important field to consider rehabilitation services. An increasing number of children born are admitted to the NICU with complications commonly related to low birth weight, premature birth, and development of underlying diseases. Early initiation of rehabilitation services in the NICU has become more common and includes therapies relating to feeding tube removal and pulmonary breathing. We investigated the patterns of rehabilitation utilization (rehabilitation frequency, moving to an area for rehabilitation treatment) and medical expenses based on NICU hospitalization history. Data from the Korean National Health Insurance Service Database over a span of ten years were reviewed, with an observation period of 3 years after the first rehabilitation session. The newborns were divided into two groups: 16,626 in the NICU group and the non-NICU group, matched 1:1 based on NICU hospitalization history. The number of rehabilitation treatments in the non-NICU group was significantly higher over the two years following the initial rehabilitation session (p < 0.05). In contrast, the total medical expenses during the 6 months following the initial rehabilitation session were more than six times higher in the NICU group (KRW 1,868,516 vs. 11,348,940, p < 0.0001). The NICU group showed significantly more discrepancies between their residence and the first rehabilitation treatment area (9.5% vs. 13.4%, p < 0.001). Results indicate that the amount of rehabilitation sessions and access to rehabilitation for individuals with a NICU history is lower compared to those without a NICU history. Therefore, national support is needed to revitalize rehabilitation procedures and reduce medical expenses in the NICU group, and further studies should focus on novel methods to revitalize NICU rehabilitation.